Teori Warna: Penerapan Lingkaran Warna dalam Berbusana - Meilani Meilani (Humaniora, 2013)
Understanding and application of color theory in the color wheel to create a harmonious color has been researched and developed from ancient times. Until now, the color theory that often used by practitioners of design like, graphic designer, interior designer, fashion designer and etc, based on the color theory by Prang. Simplifying color theory made by Prang makes his theory as a reference in creating harmonious color combinations. Now, the discussion of harmonious color combinations is in fashion matching appearance. Looks is the first impression in socializing with other people, with an understanding of color and aesthetic intuition of good matching, will create an attractive and not-boring appearance. In addition to improving mood, good cloth matching can also help a person to appear more attractive. Of course, such expertise cannot be obtained in a short time, it takes some extra knowledge in addition to understanding harmonious color combinations theory in general. We must consider other factors such as how to recognize skin color that will sustain the intensity of the color selection for our appearance. Hopefully, with this writing, the reader can see and learn a fashion matching appearance better.